Relationship between mental health and substance abuse on COVID-19 vaccine hesitancy in youth: A mixed methods longitudinal cohort study. - Louis Everest; Joanna Henderson; Clement Ma; Matthew Prebeg; Jacqueline Relihan; Lisa D Hawke (PLoS ONE)
Background Mental health and substance use challenges are highly correlated in youth and have been speculated to be associated with COVID-19 vaccine hesitancy. Literature has also suggested that mental health challenges in youth have increased during the COVID-19 pandemic. However, the longitudinal relationship between mental health challenges in youth and COVID-19 vaccine hesitancy is not well established. Objective We examined the relationship between mental health, substance use and COVID-19 vaccine hesitancy in youth during the COVID-19 pandemic. Methods Youth ages 14 to 29-years participated in a longitudinal survey study. Participants provided sociodemographic, mental health, and substance use data, as well as qualitative and quantitative information on their vaccine perspectives every two months between February 2021 to August 2021, and on February 2022. Generalized estimating equation logistic regression models were used to analyze the effect of mental health and substance use on vaccine hesitancy over time. Qualitative content area analyses were used to identify trends in vaccine attitudes. Results Mental health challenges and substance use frequency were associated with vaccine hesitancy, and significantly increased the odds of vaccine hesitancy over time. Additionally, mental health challenges were associated with decreases in vaccine hesitancy (OR: 0.80 (95% CI 0.66, 0.97)) when vaccines first began to emerge, but increases in vaccine hesitancy (OR: 1.72 (95% CI 1.32, 2.26)) one year later. Participants reported perceptions regarding vaccine safety and efficacy were the primary determinants influencing hesitant, uncertain, and acceptant vaccine attitudes. Additionally, changes in vaccine attitudes over time for some participants, were associated with changes in mental health. Conclusions Increases in mental health challenges and substance use were associated with increases in COVID-19 vaccine hesitancy in youth over the COVID-19 pandemic. Health policy agencies should be aware of the potential impact of mental health challenges and substance use in youth, when developing vaccine policy and programs.